EVALUATION OF INTERNAL CONTROL STRUCTURE OF PERSONNEL SERVICES AT SHARP ELECTRONIC INDONESIA YOGYAKARTA BRANCH - Hartati, Sri; Nursasmita., Akuntan, Drs. H. Irfan (Accounting, 2009)
Internal control structure includes organizational structure, method and size are coordinated to maintain the wealth of the organization, check the accuracy and reliability of the organization´s accounting data, promote efficiency and encourage compliance with management policies. The purpose of the internal control structure based on the definition are: (1) maintain the organization´s wealth, (2) check the accuracy and reliability of accounting data, (3) promote efficiency, and (4) encourage the patuhinya management policy. PT. SHARP ELECTRONICS INDONESIA Yogyakarta Branch has two main principles of sincerity and creativity as well as three supporting principles of harmony, civility and truth also requires a sound internal control structure .. Thus the application of the internal control structure of personnel services is necessary for employees to work well in accordance with their respective functions. The results of research the author of personnel services system run by PT SHARP ELECTRONIC INDONESIA Yogyakarta Branch is covering present time recording procedures, payroll processing procedures and salary payment procedures. Through the research stage, payroll systems and procedures in PT. SHARP ELECTRONICS INDONESIA been going pretty well and are adequate. It is known by the organizational structure which shows a separation of functions and clear responsibilities, authority and procedures for recording systems that provide adequate protection against property, debts, income and expenses and a healthy practice in carrying out its duties and functions within each organizational unit. Keywords: Internal Control Structure.